Sulfur isotopes track the global extent and dynamics of euxinia during Cretaceous Oceanic Anoxic Event 2. - Owens, J; Gill, B; Jenkyns, H; Bates, S; Severmann, S; Kuypers, M; Woodfine, R; Lyons, T (2013)
The Mesozoic Era is characterized by numerous oceanic anoxic events (OAEs) that are diagnostically expressed by widespread marine organic-carbon burial and coeval carbon-isotope excursions. Here we present coupled high-resolution carbon- and sulfur-isotope data from four European OAE 2 sections spanning the Cenomanian-Turonian boundary that show roughly parallel positive excursions. Significantly, however, the interval of peak magnitude for carbon isotopes precedes that of sulfur isotopes with an estimated offset of a few hundred thousand years. Based on geochemical box modeling of organic-carbon and pyrite burial, the sulfur-isotope excursion can be generated by transiently increasing the marine burial rate of pyrite precipitated under euxinic (i.e., anoxic and sulfidic) water-column conditions. To replicate the observed isotopic offset, the model requires that enhanced levels of organic-carbon and pyrite burial continued a few hundred thousand years after peak organic-carbon burial, but that their isotope records responded differently due to dramatically different residence times for dissolved inorganic carbon and sulfate in seawater. The significant inference is that euxinia persisted post-OAE, but with its global extent dwindling over this time period. The model further suggests that only ~5% of the global seafloor area was overlain by euxinic bottom waters during OAE 2. Although this figure is ~30× greater than the small euxinic fraction present today (~0.15%), the result challenges previous suggestions that one of the best-documented OAEs was defined by globally pervasive euxinic deep waters. Our results place important controls instead on local conditions and point to the difficulty in sustaining whole-ocean euxinia.